Mask continuous positive airway pressure increases diaphragm thickening fraction in healthy subjects - Lindner, Simon; Teichert, Jan; Hoermann, Clara; Michels-Zetsche, Julia D.; Herth, Felix; Dürschmied, Daniel; Britsch, Simone (Respiration, 2024)
Introduction: The most widespread treatment for obstructive sleep apnoea and obesity hypoventilation syndrome is continuous positive airway pressure (CPAP). The addition of inspiratory support is a potential alternative. This is a physiological study to determine the effect of CPAP and inspiratory support pressure on respiratory effort measured by diaphragm thickening fraction (DTF) in healthy volunteers. Methods: DTF was measured in spontaneously breathing, healthy volunteers during 4 phases: (I) without connection to a ventilator, (II) on a ventilator without any applied pressures, (III) with a CPAP of 5 cmH2O, and (IV) with an additional inspiratory support pressure of 5 cmH2O. Results: Twenty-nine individuals agreed to participate. DTF was similar during the first two phases (32 ± 13% and 35 ± 22%). A considerable increase in DTF to 51 ± 21% was noted in phase III. The introduction of inspiratory support pressure during phase IV led to a reduction in DTF back to 36 ± 23% (p < 0.001). Tidal volume and minute ventilation were both slightly higher in phase IV compared to phase III. Conclusion: CPAP without inspiratory support pressure increases respiratory effort measured by DTF in healthy subjects. Further research is required to investigate this phenomenon in a clinical setting.